(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
The article analyzes the Turkmen dutar performance art as a phenomenon of intangible cultural heritage. The main attention is paid to two traditional schools - Akhal and Mary, each of which has unique stylistic features. The purpose of the study is to identify the characteristic features of dutar performance, compare the differences between the schools and trace the process of institutionalization and professionalization of dutar music in the 20th-21st centuries. The work examines the structural and acoustic features of the dutar, traditional methods of oral transmission of knowledge and the role of masters in the formation of the musical culture of Turkmenistan. A comparative analysis of the styles of the Akhal and Mary schools reveals parameters such as improvisation, adherence to canons and the development of an individual style. Particular attention is paid to the influence of educational institutions, radio broadcasting and musical notation on the transformation of the dutar tradition. Despite academization, the performing tradition maintains a connection with oral transmission, which ensures the continuity of generations. The results may be useful in ethnomusicology, music education and protection of intangible heritage. The author emphasizes the importance of further support for dutar art to strengthen cultural identity.